Bonds, currencies and expectational errors - Eleonora Granziera; Markus Sihvonen (Norges Bank, 2020)
We propose a model in which sticky expectations concerning shortterm interest rates generate joint predictability patterns in bond and currency markets. Using our calibrated model, we quantify the effect of this channel and find that it largely explains why short rates and yield spreads predict bond and currency returns. The model also creates the downward sloping term structure of carry trade returns documented by Lustig et al. (2019), difficult to replicate in a rational expectations framework. Consistent with the model, we find that variables that predict bond and currency returns also predict survey-based expectational errors concerning interest and FX rates. The model explains why monetary policy induces drift patterns in bond and currency markets and predicts that long-term rates are a better gauge of market's short rate expectations than previously thought.
hdl:11250/2659880
Keywords: E43; F31; D84; 330; Bond and currency premia; sticky expectations; interest rateforecast errors